The Urgency of Determining Commercial Value of Copyright as Property Rights - Handiriono, Raden; Hardjowikarto, Dharliana; Kamil, Insan (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Copyright is a form of legal protection for works of creation produced by individuals or groups, whether in the form of scientific, literary, artistic, technological works. Copyright grants exclusive rights to creators to regulate, utilize, and obtain economic benefits from the works they have created. However, although copyright has been recognized as a property right that can be traded or licensed, in reality, creators often face major obstacles in determining the commercial value of their creations. Determining the commercial value of copyright as a property right is a solution, both in terms of protecting the economic rights of copyright owners and in encouraging the growth of creative industries based on intellectual works. This study aims to examine the urgency of determining the commercial value of copyright as a property right and to provide an ideal legal formulation to support the determination of such commercial value. The method used in this study is the normative juridical method, by analyzing applicable laws and regulations, legal doctrines, and analyzing legal theories related to copyright and commercial value. The results of the study indicate that the determination of commercial value on copyright as a property right has a very high urgency in increasing the protection of economic rights for creators and supporting the development of the creative industry in Indonesia. The ideal regulation regarding the determination of the commercial value of copyright must include a license agreement, strong legal protection, and standards for assessing works of creation by involving copyright appraisers or competent institutions in determining the economic value of a work. Determining a clear commercial value will provide balanced economic benefits for creators and parties who use the work of creation.